PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI DI ERA DIGITAL - Marhamah Marhamah; Irma Juliyanti Sitorus (Universitas Baturaja, 2024)
With the development of internet technology in the era of digitalization in a changing world, even in all sectors in company life it has become significant, not only in the marketing sphere. Lots of entrepreneurs have successfully promoted their products on Instagram social media and the many strategies they use to promote them. By using social media like Instagram, their products will be better known. This study uses a qualitative method . The results of this study are the strategy of using social media to become a tool or intermediary in promoting products more quickly and easily without even incurring large costs. The benefits of using Instagram social media as a promotional medium are that Instagram can increase potential in marketing and even become an alternative solution which is very good to be used as promotional media.